Modes of Non-invasive Respiratory Support Devices and their Significance in the Treatment of COVID-19 - Dabadi, Sambardhan; Dhungel, Raju Raj; Acharya, Saugat; Poudel, Pratik; Jha, Anik; Shrestha, Jitesh (Annapurna Journal of Health Sciences, 2023)
Introduction: The Novel Coronavirus pandemic (COVID-19) is threatening people all over the world. Each country worldwide has been affected by COVID-19 and over 300 million people have lost their lives. Acute Respiratory Failure (ARF) is the main complication for COVID-19 patients.Various oxygen therapy devices such as oxygen concentrator, high flow nasal cannula, positive airway devices like continuous positive airway pressure (CPAP), bilevel positive airway pressure (BiPAP) have much helped the patients to recover from the ARF. The use of these technology made it possible to avoid the severity of the disease and, consequently, the need for invasive ventilation and an intensive care unit (ICU).Different ways and techniques of using such devices and their significance have been mentioned in this study.